Proteomic Analysis of Liver Preservation Solutions Prior to Liver Transplantation - KAZAN, DİLEK (BENTHAM SCIENCE PUBL LTD, 2019)
Objective: Transplantation is the preferred treatment for patients with end-stage liver diseases. However, in clinical practice, functional preservation of the liver is a major concern before the transplantation. Although various protective solutions are used (in combination with hypothermia), the functional preservation time for liver is still limited to hours. We analyzed the preservation medium to detect the proteins released from the liver during storage period. Material/Methods: Samples were collected from the pre-transplant preservation mediums of 23 liver donors. For all donors, the cases involved Donation after Brain Death (DBD). 2D-PAGE and LCMSMS methodologies were used to detect the proteins and peptides from the preservation mediums. Results: A total of 198 proteins originating from the liver were detected. Conclusion: The data provide valuable insights into biomarkers that may be used to evaluate organ injury, functional status, and suitability for transplantation. Additionally, the findings could be valuable for the development of new strategies for effective preservation of solid organs prior to transplantation.
Keywords: Liver; mass spectrometry; organ preservation solution; proteomics; liver transplantation; hypothermia; ISCHEMIA-REPERFUSION INJURY; GLUTATHIONE-S-TRANSFERASE; GRAFT FUNCTION; COLD ISCHEMIA; UW SOLUTION; EXPRESSION; ARGINASE; ENZYME; ALPHA; CELLS